KEBIJAKAN ATAS KEWAJIBAN E-FILLING DALAM PENYAMPAIAN SPT TAHUNAN BAGI ASN/TNI/POLRI DAPAT DITERAPKAN DI SELURUH WILAYAH INDONESIA - Nasution, Dito Aditia Darma; Alpi, M. Firza (Universitas Pembangunan Panca Budi, 2025)
Submission of a Tax Return is one of the taxpayer’s obligations. Based on Law of the General Provisions and Tax Procedures Article 6, there are several ways to submit Tax Return. They are to submit directly, by post or by other means regulated by decree of the Minister of Finance. However MENPAN RB issued Circular Number 8 of 2015 concerning the Obligation of Submiting Annual Tax Returns for Individual Taxpayers by State Civil Aparatus / Members of Indonesian National Army/Indonesian Repulic Police through e-filing. The purpose of this study is to evaluate whether this policy can be applied in all regions of Indonesia. This research is a descriptive one with a qualitative approach. Based on the data, internet has not reached all of regions in Indonesia and many internet users do not have the knowledge to implement e-filing. The unavailability of taxpayers' infrastructure and knowledge to carry out e-filing, creates difficulties for taxpayers. The results of this researach will be useful to improve next related policies.